Performance Measurement of the Impact of Social Return on Investment (SROI) of the Jayakarta Agro-Educational Tourism Program of PT XYZ - Razak, Rizal; Matoati, Rindang; Amelia, Thamya; Septiani, Siti Vina Rahma (Sam Ratulangi University, 2025)
The impact analysis of PT XYZ Corporate Social Responsibility (CSR) program using the Social Return on Investment (SROI) method focuses on the company's flagship initiative, the Agro-Educational Tourism Jayakarta program, located in Jatinegara Kaum Village, Pulo Gadung District, East Jakarta. This program has been a collaboration between PT XYZ and the Rumah Kaum Jayakarta Forest Farmers Group (KTH) since 2021. The impact assessment utilized both quantitative and qualitative data collected through periodic financial reports, in-depth interviews, and focus group discussions (FGD). The SROI value of the Agro-Educational Tourism Jayakarta program was 3,58, indicating that every one rupiah invested by PT XYZ generated 3,52 rupiah of economic, social, and environmental benefits. The total net benefit, after a 15% deadweight adjustment, amounted to Rp4.928.800.674 over the 2021–2023 period. The identified benefits include: (a) enhanced horticultural cultivation skills, (b) increased income from horticultural product sales, (c) strengthened social capital such as cohesion and solidarity, (d) reduced organic and inorganic waste through maggot cultivation and creative recycling, and (e) the emergence and dissemination of environmental awareness movements. The total CSR investment under the empowerment category for this program reached Rp1.399.345.270 over three years (2021–2023). The Agro-Educational Tourism Jayakarta program effectively addressed local waste management challenges by establishing an integrated waste management system to minimize waste generation, environmental degradation, flood risk, and disease. The program also introduced an innovative system that transformed waste into a savings-based investment tool, integrating it with environmental preservation through fun-learning-based educational tourism packages designed to foster